2019
DOI: 10.1088/1367-2630/ab1c3b
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of solute deuterium in titanium deuteride by atom probe tomography with both laser pulsing and high-voltage pulsing: influence of the surface electric field

Abstract: Atom probe tomography (APT) has been increasingly used to investigate hydrogen embrittlement in metals due to its unique capacity for direct imaging of H atoms interacting with microstructural features. The quantitativeness of hydrogen measurements by APT is yet to be established in views of erroneous compositional measurements of bulk hydrides and the influence of spurious hydrogen, e.g. residual gas inside the analysis chamber. Here, we analyzed titanium deuteride (approx. 65.0 at%-66.6 at% D) in lieu of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 60 publications
(89 reference statements)
3
20
0
Order By: Relevance
“…Protecting materials against hydrogen is challenging: whereas some materials such as titanium undergo formation of brittle hydrides, others such as nickel and high-strength steels experience enhanced local plasticity and void formation. Measures that may reduce hydrogen embrittlement are the reduction of regions of high micromechanical contrast among phases and microstructure components (as hydrogen tends to enrich in highly stressed regions such as at interfaces), dense oxide surface layers which reduce hydrogen uptake, and trapping of hydrogen at semi-coherent internal interfaces and supposedly also at other defects [64][65][66] . In some cases, hydrogen trapping can be a cause of undesired local softening, such as through the stabilization of superabundant vacancies or the lowering of the activation barriers for the double-kink mechanism of dislocation motion 67,68 .…”
Section: Longevity By Corrosion Protection Lifetime Extension and Reusementioning
confidence: 99%
“…Protecting materials against hydrogen is challenging: whereas some materials such as titanium undergo formation of brittle hydrides, others such as nickel and high-strength steels experience enhanced local plasticity and void formation. Measures that may reduce hydrogen embrittlement are the reduction of regions of high micromechanical contrast among phases and microstructure components (as hydrogen tends to enrich in highly stressed regions such as at interfaces), dense oxide surface layers which reduce hydrogen uptake, and trapping of hydrogen at semi-coherent internal interfaces and supposedly also at other defects [64][65][66] . In some cases, hydrogen trapping can be a cause of undesired local softening, such as through the stabilization of superabundant vacancies or the lowering of the activation barriers for the double-kink mechanism of dislocation motion 67,68 .…”
Section: Longevity By Corrosion Protection Lifetime Extension and Reusementioning
confidence: 99%
“…Laser‐assisted field evaporation of titanium deuteride with a laser pulse energy of 10 pJ (identical energy as in the present work) revealed that the measured titanium content was reduced down to 27 at% instead of the expected 33–35 at% and explained by an increased fraction of background counts caused by significant DC evaporation. [ 21 ] The mass spectrum, shown in Figure S3, Supporting Information, also reveals a relatively high fraction of background counts and it appears reasonable to assume that the absolute gadolinium composition is therefore underestimated. Moreover, the mass spectrum exhibits mostly molecular ions and it has been demonstrated that the relative amounts depend significantly on the electrostatic field.…”
Section: Evidence For Dual‐phase Formationmentioning
confidence: 99%
“…The distribution of solute hydrogen in the matrix is challenging by APT, even when D-charging is used. Quantitative analysis by APT is extremely challenging in such metallic systems [31], in particular when laser-pulsing mode is used [35] as a significant proportion of the hydrogen to be field evaporated as H2 + and overlap with the peak of deuterium, hindering quantification. To address this, we analysed a Dcharged blocky-α sample, prepared at cryogenic temperature and using cryogenic transfer and we estimated the composition using the deconvolution protocol we introduced in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Results are made complicated by the residual H from within the APT chamber which ends up being detected as part of the analysis, and by the possibility that neutral hydrogen or dihydrogen detaches from a field evaporated molecular ion during the ion's flight between the specimen and the single-particle position-sensitive detector used in the atom probe. For the characterization of Zr-based alloys, we discussed these issues in details in Mouton et al [31,35], where we also introduced a protocol to correct the composition profiles to account for some of these issues. These methods were also used here, and the interested readers are encouraged to refer to this previous study.…”
Section: Atom Probe Tomography Characterizationmentioning
confidence: 99%